Magnon crystals and magnetic phases in a kagome-stripe antiferromagnet - Acevedo, Santiago Daniel (2019)
In this paper we analyze the magnetization properties of an antiferromagnetic kagome-stripe lattice, motivated by the recent synthesis of materials exhibiting this structure. By employing a variety of techniques that include numerical methods such as density-matrix renormalization-group and Monte Carlo simulations, as well as analytical techniques such as perturbative low-energy effective models and exact solutions, we characterize the magnetization process and magnetic phase diagram of a kagome-stripe lattice. The model captures a variety of behaviors present in the two-dimensional kagome lattice, which are described here by analytical models and numerically corroborated. In addition to the characterization of semiclassical intermediate plateaus, it is worth noting the determination of an exact magnon crystal phase which breaks the underlying symmetry of the lattice. This magnon crystal phase generalizes previous findings